Refractory thrombotic thrombocytopenic purpura related to checkpoint inhibitor immunotherapy. Issue 1 (29th October 2020) - Lancelot, Moira; Miller, Maureen J.; Roback, John; Stowell, Sean R.
Abstract: Background: Checkpoint inhibitors enhance T‐lymphocyte–mediated antitumor responses, resulting in increased survival for patients with neoplastic disease. However, a subset of patients receiving checkpoint inhibitor therapy may experience adverse complications that include the development of autoimmune conditions, such as thrombotic thrombocytopenic purpura (TTP). Given the potential etiologic differences of checkpoint inhibitor–related autoimmunity, TTP that develops in the presence of checkpoint inhibitors may be refractory to current treatment methods and therefore may require additional treatment and prognostic consideration. Case Report: Herein, we describe the unique clinical course of a patient who was treated with the combined checkpoint inhibitors nivolumab and ipilimumab for Stage IV malignant melanoma, who subsequently developed TTP. Unlike many patients with TTP, this patient failed to develop a sustained response to therapeutic plasma exchange. Additional use of steroids, anti‐CD20, and plasma cell–targeting therapy (bortezomib) also failed to substantially reverse thrombocytopenia in a sustainable fashion. During this time, her melanoma progressed, and she ultimately succumbed. Conclusion: This case illustrates not only that TTP may be a potential complication of checkpoint inhibitor therapy, but also that TTP developing in this setting may result in an unpredictable response to commonly employed TTP treatment modalities. Ultimately, checkpoint inhibitor–related TTP may require distinct management approaches and prognostic considerations.